Sand-geotextile interface characterisation through monotonic and cyclic direct shear tests - Castorina Silva Vieira (2013)
For the design and performance analyses of geosynthetic-reinforced soil structures under repeated loading, such as those induced by compaction, traffic and earthquakes, the understanding of cyclic soil-geosynthetic interface behaviour is of great interest. Nevertheless, experimental data concerning this type of behaviour are very scarce. A laboratory study was carried out and is described in this paper. This paper presents the behaviour of an interface between a silica sand and a high-strength geotextile under monotonic and cyclic loading conditions. A large-scale direct shear test device able to perform load-or displacement-controlled cyclic tests was used. The results obtained are presented and discussed, especially in terms of interface shear stiffness and damping ratio. Monotonic direct shear tests indicated that the coefficients of interaction for the sand-geotextile interface depend on the confining pressure. Cyclic direct shear tests indicated that the interface stiffness tends to increase during the first loading cycles, exhibiting slight variation after 10 cycles. Slightly higher values of shear stiffness and damping ratio were reached with displacement-controlled cyclic direct shear tests. The cyclic loading of the interface did not lead to the degradation of the post-cyclic peak shear strength; however, the post-cyclic shear strength for large displacements exhibited an important decrease.